PERTANGGUNGJAWABAN PENITIPAN MOBIL PADA SAAT PERBAIKAN DI DEALER BENGKEL PT. ASTRA INTERNATIONAL TBK CABANG AUTO 2000 GATOT SUBROTO KOTA MEDAN - razokitta saragih; suhaidi; rosnidar (Magister Hukum Universitas HKBP Nommensen, 2021)
The car storage agreement in the process of repair is included in the type of true goods safekeeping agreement that occurs with an agreement or agreement set forth in the form of a standard agreement (standard agreement). The purpose of making a standard agreement or standard agreement for car care in the repair process is to provide convenience for the parties concerned. The research was conducted using normative juridical and empirical juridical, descriptive analytical research is research that aims to describe a situation or symptom or to determine whether there is a relationship between a symptom and other symptoms. Data collection techniques used are literature studies and field studies in the form of data collection and interviews with the PT. Astra International Tbk Auto 2000 Branch and customers. Astra International Tbk Auto 2000 Branch is obliged to maintain and protect cars that are entrusted in the repair process and are entitled to legal protection from the actions of customers who have bad intentions. Responsibilities of PT. Astra International Tbk Auto 2000 Branch in the event ofdamage to the car that was deposited during the repair process, compensation is given. The value of the compensation provided by the PT. Astra International Tbk Auto 2000 Branch to the customer who is damaged or lost the car in the process of repair, it is determined in accordance with the stipulated provisions and by family. The settlement process due to the car being deposited is damaged during the safekeeping process for repairs, where both parties agree to settle the dispute as far as possible by way of deliberation. If deliberation has been carried out by both parties, but it turns out that it does not succeed in reaching an agreement, the parties agree that all disputes arising from this agreement will be resolved at the Registrar's Office of the Medan District Court.